A principled framework for the autonomy of religious communities: reconciling freedom and discrimination - Deagon, Alex (Hart, 2023)
"This book engages in a theological critique of the legal frameworks and theoretical approaches of Australia, the US and England to create a peaceful coexistence of difference which supports both religious freedom and equality. It develops a new framework for reconciling religious freedom and discrimination in Western liberal democracies and presents a unique approach to practically supporting both religious freedom and equality as fundamentally important objectives which promote more compassionate and cohesive communities. The book applies the idea of peaceful coexistence of difference by assuming the dignity and goodwill of different people and perspectives, and proceeds upon shared virtues such as love which are affirmed by all"--